LEADING SECTOR ANALYSIS IN IMPROVING ECONOMIC GROWTH (Case Study in South Halmahera District, North Maluku) (JURNAL ECONOMICA : Research of Economic And Economic Education, 2021)
Leading Sectors in Order to Increase Economic Growth in South Halmahera Regency. The aim of this research is to identify the leading sectors in order to increase the economic growth of South Halmahera Regency. The analysis was carried out using the Location Quotient and Klassen Typology methods. From the results of the location quotient analysis, there are 13 leading sectors, namely agriculture, forestry and fisheries, mining and quarrying, processing industry, electricity and gas procurement, water supply, waste management, waste and recycling, construction sector. , the wholesale and retail trade sector; car and motorcycle repair, the transportation and warehousing sector, the financial services sector and insurance, the real estate sector, the education services sector, and the health services and social activities sector, and the last sector, namely the other service sector. and analysis of typology classifications, there are three categories, namely the electricity and gas procurement sector, the water supply sector, waste management, waste and recycling, the accommodation and food and beverage provision sector, the real estate sector, the corporate services sector and the other services sector. is a sector that is classified as a developed and rapidly growing sector, while the information and communication sector, the financial services and insurance sector, the health services sector and social activities, the construction sector, and the education services sector are in the category of potential or can still develop. and the government administration, defense and compulsory social security sector, the wholesale and retail trade sector; car and motorcycle repair, the manufacturing sector, and the agriculture, forestry and fisheries sectors of these four sectors are in the relatively underdeveloped sector category.